Terpaan Pemberitaan Media dalam Mengamplifikasi Persepsi Risiko Bahaya Gempa Megathrust di Indonesia - Yunati Alinda; Shela Kusumaningtyas; Leoni Nindyasari; Adinda Aulia Nurhaliza (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
Media play a crucial role in disaster risk communication by shaping public understanding and perception of potential hazards. In Indonesia, intensive media coverage of the potential megathrust earthquake, particularly during the period when the issue became widely viral in mid to late 2024, raised public concern regarding the amplification of risk perception. This study examines the effect of media exposure on the amplification of risk perception related to the potential megathrust earthquake in Indonesia, with self-relevance and news credibility as moderating variables. Using a quantitative survey design, data were collected from 185 respondents and analysed using moderated regression analysis with the PROCESS Macro (Model 3) developed by Hayes to examine both direct and interaction effects. The results indicate that media exposure has a positive and significant effect on risk perception. Self-relevance strengthens the relationship between media exposure and risk perception, while news credibility moderates this relationship, particularly when self-relevance is low. The overall model demonstrates strong explanatory power (R² = 0.897), indicating a substantial contribution of the proposed variables in explaining variations in risk perception. This study contributes theoretically to the literature on risk communication and the Social Amplification of Risk Framework by demonstrating that the amplification of disaster risk perception is not solely driven by media exposure, but is contingent upon individual relevance and perceived credibility of news sources. Practically, the findings underscore the importance of responsible disaster communication strategies that balance public awareness with the prevention of excessive fear.